Kitab Kuning dan Pesantren: Peran MA Baitussalam Melestarikan Warisan Intelektual - Hasan, Ismail; Anshory, Isa (TSAQOFAH, 2024)
Kitab kuning viewed as theory and values contributor that followed al-Quran and Hadis Nabi as a background. In pesantren world, kitab kuning position are very strategic because it used as text book, references, and curriculum within pesantren education system. Aside from being religion procedure guideline, kitab kuning also functioned as universalreferences on responding every life challenge among pesantren people. This writing presents the results of research on the tradition of reading "kitab kuning" (yellow books) in Islamic boarding schools (Pondok Pesantren). The research employed a data collection method involving the reading and interpretation of various models of learning "kitab kuning" in pesantren, with a particular focus on observing Islamic Boarding School Baitussalam. The findings of this research indicate that the tradition of learning to read "kitab kuning" is still ongoing in Pondok Pesantren. The in-depth study and learning models of "kitab kuning" have become distinctive features in developing literacy and scholarly references in the world of pesantren. Classic texts, commonly known as "kitab kuning," play a crucial role in advancing the teachings of Islam. This underscores the importance of studying these yellow books. Islamic scholars have compiled these teachings into uniquely yellow-colored books, which are studied in Madrasahs and Pondok Pesantren. These books contain Islamic knowledge, particularly in the field of Islamic jurisprudence (Fikih), and are written or printed in Arabic script, using Arabic or Malay, Javanese, Sundanese, and other languages.